1975
DOI: 10.1161/01.res.36.4.513
|View full text |Cite
|
Sign up to set email alerts
|

A renin inhibitor from rabbit kidney: conversion of a large inactive renin to a smaller active enzyme.

Abstract: Renin in extracts of frozen rabbit kidney exists in two forms: active (molecular weight about 37,000) and inactive (molecular weight about 55,000) renin. The inactive form becomes active after exposure to pH 2.5 at 4°C. If extracts are chromatographed on DEAE cellulose, the inactive renin dissociates into active renin plus a renin inhibitor (molecular weight about 13,000). The inhibitor recombines with active renin if the two are incubated together at 37°C. The inhibitor is destroyed by acid treatment at pH 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(34 citation statements)
references
References 21 publications
4
30
0
Order By: Relevance
“…Leckie, 1973;deSenarclens et al, 1977;Skeggs et al, 1967). The studies of Leckie and McConnell (1975) suggest that inactive renin may be coupled to an inhibitor, which is destroyed by acidification. Most studies on experimental animals to date have concentrated on the estimation of tissue renin content, although James and Hall (1974) did measure acidactivated renin in dog plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leckie, 1973;deSenarclens et al, 1977;Skeggs et al, 1967). The studies of Leckie and McConnell (1975) suggest that inactive renin may be coupled to an inhibitor, which is destroyed by acidification. Most studies on experimental animals to date have concentrated on the estimation of tissue renin content, although James and Hall (1974) did measure acidactivated renin in dog plasma.…”
Section: Discussionmentioning
confidence: 99%
“…This acid-activated or inactive renin* has also been reported to be present in several species in addition to man (Boyd, 1974;Rubin, 1972;Leckie, 1973;deSenarclens et al, 1977;James and Hall, 1974;Skeggs et al, 1967). Whether inactive renin represents a true proenzyme or renin bound to an inhibitor remains unclear (Leckie and McConnell, 1975). It also has been suggested that inactive renin may be the intrarenal storage form of the enzyme (deSenarclens et al, 1977) Acid-activated renin has been measured in systemic and renal venous plasma of man under varying conditions (Derkx et al, 1976;Weinberger et al, 1977).…”
Section: Release Of Active and Inactivementioning
confidence: 99%
“…The reason for this is not immediately apparent, unless the renin-60 is a combination of renin and a bound protein, as reported by Boyd 18 and Leckie and McConnell. 19 If this is the case, it may be that the presence of the protease inhibitors stabilized some other protein which is involved in the conversion of renin-60 to renin-40. If the binding protein in the presence of the protease inhibitors is more labile than renin (as it is at pH 3.3, 18 l9 or possibly even in the cold 12 ' l3 ), relatively more of it would be denatured, thus leaving an insufficient amount to bind all the remaining renin.…”
Section: Figure 10 Renin-specific Activity As a Junction Of Crude Extmentioning
confidence: 99%
“…The unusually high proportion of inactive renin in plasma and tumor extracts from such patients is consistent with ineffective precursor processing by neoplastic tissue, suggesting that if activation of "prorenin" is involved in the normal regulation of active renin levels it more likely Introduction Renin (EC 3.4.99. 19) is a proteolytic enzyme that is found most abundantly in the kidney. Renal renin is secreted into the circulation, where it catalyzes the rate-limiting step in the formation of the vasopressor and aldosterone-stimulating peptide angiotensin II.…”
mentioning
confidence: 99%
“…Inactive renin has several characteristics of a biosynthetic precursor of renin (8,12,13). Other evidence has been cited to support the view that it may be a postsynthetic modification ofactive renin (15)(16)(17), especially since, in renal cortical extracts from several species, renin can form a large molecular weight complex with a polypeptide binding substance (18)(19)(20). However, these complexes are enzymatically active and thus differ from the completely inactive substance found in human plasma (8).…”
mentioning
confidence: 99%